2021
DOI: 10.7554/elife.70361
|View full text |Cite
|
Sign up to set email alerts
|

CRMP4-mediated fornix development involves Semaphorin-3E signaling pathway

Abstract: Neurodevelopmental axonal pathfinding plays a central role in correct brain wiring and subsequent cognitive abilities. Within the growth cone, various intracellular effectors transduce axonal guidance signals by remodeling the cytoskeleton. Semaphorin-3E (Sema3E) is a guidance cue implicated in development of the fornix, a neuronal tract connecting the hippocampus to the hypothalamus. Microtubule-Associated Protein 6 (MAP6) has been shown to be involved in the Sema3E growth-promoting signaling pathway. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Besides these small molecules, Plexins can also interact with other molecules such as collapsin-response mediator proteins (CRMPs). CRMP4 has been found to interact with Sema3E tripartite receptor complex and its cytoskeleton-binding domain is required for Sema3E’s axon growth-promoting activity ( Boulan et al, 2021 ). We have demonstrated that CRMP4 is critical for zebrafish retinal axon growth and guidance ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these small molecules, Plexins can also interact with other molecules such as collapsin-response mediator proteins (CRMPs). CRMP4 has been found to interact with Sema3E tripartite receptor complex and its cytoskeleton-binding domain is required for Sema3E’s axon growth-promoting activity ( Boulan et al, 2021 ). We have demonstrated that CRMP4 is critical for zebrafish retinal axon growth and guidance ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAP6 (also known as STOP) is a versatile regulator of neuronal connectivity that was first identified as a MT stabilising protein required for MT protection against cold-and nocodazole-induced depolymerisation [130,131]. Neuroanatomical analysis of MAP6 knockout brains reveals substantial hypoplasia of several commissures and axonal tracts, including the absence of the post-commissural part of the fornix [132][133][134]. Regarding this latter phenotype, MAP6 is required for the Sema3E-induced axon outgrowth of subicular neurons (i.e.…”
Section: Ii22 Structural Maps In Axon Guidance: More Than Just Mt Sta...mentioning
confidence: 99%